Reliability based robustness of timber structures through NDT data updating - Sousa, Hélder S. (2011)
This work presents a framework for reliability-based assessment of timber structures / members using data gathered from non-destructive test results. These results are used for modeling an update of the mechanical characteristics of timber, using Bayesian methods. These methods are suitable to be used for parameter estimation and also allow updating model uncertainties. From the updated model, decisions upon the life-cycle reliability of existing structures may be taken and maintenance or strengthening actions may be considered. In this work, results gathered from ultrasound testing, Resistograph® and Pilodyn® conducted on chestnut wood specimens were used, as well as correlations between those results and compression strength parallel to the grain tests’ results. The resistant characteristics are also updated assuming deterioration models applied to specific key elements of the structure, thus, being possible to evaluate reliability based in time dependent factors, as well to categorize that structure in terms of robustness.